Subnational government bailouts in Germany - Helmut Seitz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
The paper presents an investigation of subnational government bailouts in Germany. In a first part we briefly describe the fiscal federalism system in Germany. The main part of the paper examines the bailout of two West German states. We identify the causes of the financial trouble of both states and examine the institutional settings that forced the federal government to provide bailout transfers. In addition, we investigate the impact these transfers had on the fiscal performance of both Länder. In a further section we provide evidence on bailouts of local governments by the German Länder. A final section summarizes our results and presents policy conclusions.
Keywords: 330; Finanzausgleich; Staatsbankrott; Öffentlicher Transfer; Deutschland; Bremen (Land); Saarland